ACCOUNTING INSTRUCTION IN FRANCE. - Wasserman, Max J. (The Accounting Review, 1932)
Accounting does not occupy the honored position in the French system of education which falls to its lot in the United States. The French make but little provision for it and do this in what appears to some a grudging manner. The French schools undertake the preparation of young Frenchmen and Frenchwomen for citizenship in a highly centralized democracy with aristocratic and monarchic traditions. The French school system is under the direct supervision and control of the Ministry of Public Instruction and comprises two classes of establishment: public and private. The professors in these institutions are appointed by the national or local authorities after a competitive examination, while the nomination of professors by the private schools is subject to the approval of the Minister of Public Instruction. Accountancy is not taught there by what they might term the textbook method, so popular in many American institutions of higher learning. A combination of lectures and laboratory practice is used. The lectures are of a high calibre viewed from both form and content and if taken down as delivered, would form a respectable manual for the course.